2016
DOI: 10.1155/2016/6012761
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Evaluating the Cardiotoxicity of Traditional Chinese Medicine Compatibility by Using Support Vector Machine Model Combined with Metabonomics

Abstract: Traditional biochemical and histopathological tests have been used to evaluate the safety of traditional Chinese medicine (TCM) compatibility for a long time. But these methods lack high sensitivity and specificity. In the previous study, we have found ten biomarkers related to cardiotoxicity and established a support vector machine (SVM) prediction model. Results showed a good sensitivity and specificity. Therefore, in this study, we used SVM model combined with metabonomics UPLC/Q-TOF-MS technology to build … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…FTB is considered a non-toxic or low toxic herb for the past several thousands of years with a recommended dose of 5−10 g (equivalent to 83–167 mg/kg body weight) for adults [2]. Recently, three included studies were published which are relevant to the toxicity of FTB [79,81,92]. An in vivo study using 110 male Wistar rats indicated that the FTB water extract (10 g/kg, ig, for seven days) did not increase the creatine kinase and lactate dehydrogenase levels compared to the saline group [79].…”
Section: Modern Exploration Of Ftbmentioning
confidence: 99%
See 1 more Smart Citation
“…FTB is considered a non-toxic or low toxic herb for the past several thousands of years with a recommended dose of 5−10 g (equivalent to 83–167 mg/kg body weight) for adults [2]. Recently, three included studies were published which are relevant to the toxicity of FTB [79,81,92]. An in vivo study using 110 male Wistar rats indicated that the FTB water extract (10 g/kg, ig, for seven days) did not increase the creatine kinase and lactate dehydrogenase levels compared to the saline group [79].…”
Section: Modern Exploration Of Ftbmentioning
confidence: 99%
“…Recently, three included studies were published which are relevant to the toxicity of FTB [79,81,92]. An in vivo study using 110 male Wistar rats indicated that the FTB water extract (10 g/kg, ig, for seven days) did not increase the creatine kinase and lactate dehydrogenase levels compared to the saline group [79]. The histopathological examination in this study showed that the basic structure of heart tissue and cardiac muscle fibers were normal, compared to the saline group.…”
Section: Modern Exploration Of Ftbmentioning
confidence: 99%
“…In more advanced moves, a Chinese team used deep-learning algorithms to create an AI agent capable of accurately and efficiently supporting the screening of congenital cataracts as well as the treatment decisions by ophthalmologists across multiple hospitals [4]. Other AIM research projects coming from China have touched on the feasibility of using support vector machine model combined with metabonomics to check the safety of traditional Chinese medicine [43], or applying computational methods such as data mining to modernize traditional Chinese pharmacy [44,45,46,47]. By comparison, AIM studies in Japan show an advanced level in the physical branch, such as the successful robot assistance in thoracoscopic surgery [48], elderly care [49,50], or the health exercise demonstration robot TAIZO that can encourage more people to work out [51].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The active toxic alkaloids are liposoluble; thus, the DDA content in nonpolar solvent extracts is higher than that in aqueous solvent extracts. At present, there are few studies on the extraction of FZ alkaloids, most of which focus on extraction using boiling water or soaking, and extraction using alcoholic solvents [ 14 ].…”
Section: Introductionmentioning
confidence: 99%